Federalism and Climate Governance in Pakistan: Accessing Strategies, Responses and Implementation Challenges to Environmental Devolution after 18th Amendment - Maleeha Asghar; Muhammad Manzoor Elahi; Dr. Fouzia Ghani (Indus Journal of Social Sciences, 2025)
In modern federal state system, environmental governance is one of the most important tools of sustainable development. Pakistan, as a federal state, is still far from reaching its goal of sustainable development, despite its significant steps by making laws and regulations to address environmental challenges. Pakistan scored 24.6 on the Environmental Performance Index (EPI), placing it 176th out of 180 nations in 2022. However, 18th constitutional amendment is a landmark achievement that devolves powers to sub-national units for environmental governance. This research, therefore, examines the implementation strategies, challenges and responses after 18th constitutional amendment to promote a sustainable environment governance in Pakistan. By applying the qualitative explorative research design, the study conducts in-depth interviews of environmental governance officials. It draws themes and analyses data by using NVivo software. The research finds the implementation challenges to environmental devolution and recommends an increase in the financial budget of the provinces, capacity building of provincial EPA officials and inter-provincial cooperation to make 18th constitutional amendment operationalized.